2023
DOI: 10.1128/spectrum.04333-22
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Detection and Genetic Analysis of a Novel Porcine Circovirus (Porcine Circovirus 4) in Dogs in the World

Abstract: This study is the first to report the presence of PCV4 in dogs worldwide, and the first complete genome sequence was obtained from a dog affected with diarrhea. Three genotypes of PCV4 strains (PCV4a, PCV4b, and PCV4c) were determined, as supported by specific amino acid markers (V239L for open reading frame 1 [ORF1] and N27S R28G and M212L for ORF2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…The specific amino acid patterns reported by Xu et al included PCV4a (239 V in Rep, 27S, 28R and 212 L in Cap), PCV4b (239 L for Rep, 27 S, 28 G and 212 L for Cap) and PCV4c (239 V for Rep, 27 N, 28 R and 212 M for Cap). Nevertheless, in the phylogenetic tree, two strains (KU-02010 and KU-02011) belong to PCV4c, but at amino acid position 27 of Cap is S instead of N. Two strains (PCV4-PY and JXSC-2021) belong to PCV4a, but at amino acid position 212 of Cap is P instead of L. These results differ from previous studies ( Xu et al, 2022b ; Zhang et al, 2023 ), indicating the proposed classification of genotypes were not suitable. Similar to what initially occurred with PCV-2 and now occurs with PCV3 ( Segalés et al, 2008 ; Franzo et al, 2020b ), no consensus was reached and different research groups proposed independent classification criteria and protocols, leading to some confusion among veterinarians and researchers.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The specific amino acid patterns reported by Xu et al included PCV4a (239 V in Rep, 27S, 28R and 212 L in Cap), PCV4b (239 L for Rep, 27 S, 28 G and 212 L for Cap) and PCV4c (239 V for Rep, 27 N, 28 R and 212 M for Cap). Nevertheless, in the phylogenetic tree, two strains (KU-02010 and KU-02011) belong to PCV4c, but at amino acid position 27 of Cap is S instead of N. Two strains (PCV4-PY and JXSC-2021) belong to PCV4a, but at amino acid position 212 of Cap is P instead of L. These results differ from previous studies ( Xu et al, 2022b ; Zhang et al, 2023 ), indicating the proposed classification of genotypes were not suitable. Similar to what initially occurred with PCV-2 and now occurs with PCV3 ( Segalés et al, 2008 ; Franzo et al, 2020b ), no consensus was reached and different research groups proposed independent classification criteria and protocols, leading to some confusion among veterinarians and researchers.…”
Section: Discussioncontrasting
confidence: 73%
“…The multiple sequence alignment showed SCGA-Cat shared 98.2–99.0% whole genome nucleotide identity with 60 reference strains. The hosts of these reference strains include pigs, dogs, foxes and dairy cows ( Wang et al, 2022 ; Wu et al, 2022 ; Xu et al, 2022b ; Zhang et al, 2023 ), and the reference sequences were collected from different provinces of China and Korea from 2012 to 2022. In terms of geographic distribution, host and time, PCV-4 has high similarity (98.2–99.0%) among the available sequences, indicating a low variability of PCV4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two PCV4 reference strains (KU-02010 and KU-02011) from Korea, as well as one reference strain (PCV4-PY) from Henan Province, China, were classified as PCV4a in the phylogenetic tree, yet their Cap protein’s 212th position contained M and P, respectively, instead of L. This indicated that the marker positions suggested by Xu et al might not be universally applicable. GS2022-BY and GS2022-LZ also contained the essential elements for the replication of circoviruses in pig-origin PCV4 strains predicted by Nguyen et al [ 34 ], such as the origin of DNA replication, endonuclease and helicase.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, PCV4 has been widely spreading in China and other countries, and the infection rate has been increasing year by year [ 18 , 19 , 20 , 21 ]. Currently, no effective treatment or commercial vaccine is available in the domestic and foreign markets.…”
Section: Discussionmentioning
confidence: 99%